English Teacher's Written Corrective Feedback on Students with Intellectual Disabilities' Writing Assignments: A Case Study - Sahmiral Amri Raja Guk Guk; Rahmah Fithriani (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Written corrective feedback plays an important role in supporting writing development, yet limited attention has been given to how it is adapted for students with intellectual disabilities in inclusive EFL classrooms. This study aims to examine the types of written corrective feedback provided by an English teacher and to explain how feedback is adapted to meet students’ cognitive and emotional needs. Employing a qualitative case study design, data were collected from eighteen writing tasks produced by three students with intellectual disabilities and one semi-structured interview with the teacher. Document analysis was conducted using Ellis’s feedback typology, while interview data were analyzed thematically to interpret pedagogical reasoning. The findings reveal a strong predominance of direct feedback, supported by selective correction, concrete modeling, and affective language. These practices reflect feedback adaptation that regulates cognitive demand, provides clear instructional support, and sustains student motivation. The study concludes that effective written corrective feedback in inclusive EFL contexts prioritizes functional meaning, clarity, and emotional safety to support meaningful participation in writing activities.